Synthesis and enzymatic ketonization of the 5-(halo)-2-hydroxymuconates and 5-(halo)-2-hydroxy-2,4-pentadienoates - Stack, Tyler M. M.; Jr., William H. Johnson; Whitman, Christian P. (Beilstein Journal of Organic Chemistry, 2017)
5-Halo-2-hydroxymuconates and 5-halo-2-hydroxy-2,4-pentadienoates are stable dienols that are proposed intermediates in bacterial meta-fission pathways for the degradation of halogenated aromatic compounds. The presence of the halogen raises questions about how the bulk and/or electronegativity of these substrates would affect enzyme catalysis or whether some pathway enzymes have evolved to accommodate it. To address these questions, 5-halo-2-hydroxymuconates and 5-halo-2-hydroxy-2,4-pentadienoates (5-halo = Cl, Br, F) were synthesized and a preliminary analysis of their enzymatic properties carried out. In aqueous buffer, 5-halo-2-hydroxy-2,4-pentadienoates rapidly equilibrate with the β,γ-unsaturated ketones. For the 5-chloro and 5-bromo derivatives, a slower conversion to the α,β-isomers follows. There is no detectable formation of the α,β-isomer for the 5-fluoro derivative. Kinetic parameters were also obtained for both sets of compounds in the presence of 4-oxalocrotonate tautomerase (4-OT) from Pseudomonas putida mt-2 and Leptothrix cholodnii SP-6. For 5-halo-2-hydroxymuconates, there are no major differences in the kinetic parameters for the two enzymes (following the formation of the β,γ-unsaturated ketones). In contrast, the L. cholodnii SP-6 4-OT is ≈10-fold less efficient than the P. putida mt-2 4-OT in the formation of the β,γ-unsaturated ketones and the α,β-isomers from the 5-halo-2-hydroxy-2,4-pentadienoates. The implications of these findings are discussed. The availability of these compounds will facilitate future studies of the haloaromatic catabolic pathways.
Keywords: dienol; enzyme kinetics; fluoride; halogen